PERGERAKAN HARGA SAHAM AKIBAT PERUBAHAN NILAI TUKAR, INFLASI, TINGKAT BUNGA, DAN GROSS DOMESTIC PRODUCT - Shinta Heru Satoto; Sri Budiwati (University of Merdeka Malang, 2013)
The purposes of this study were to provide an empirical evidence of the influence of macroeconomic variablesand the time varying volatility phenomena on stock price. This research used manufactured firms that list onIndonesian Capital Market on 2009 until 2011 periods for the sampel. This research also used several macroeconomicsvariables such as exchange rate, inflation, BI rate, and Gross Domestic Product. The empirical resultshowed that exchange rate, BI rate, and Gross Domestic Product influenced stock price. The result also showedthat time varying volatility was happenend on stock price fluctuation. This result indicated that Indonesianstock price have high volatility on 2009 til 2011 periods